Competition with Nonexclusive Contracts: Tackling the Hold-Up Problem (2020)
In an environment in which a buyer and a seller make ex-ante investments, competition among sellers can solve the hold-up problem without the design of ex-ante contracts but, in the case of low levels of competition, this may lead to inefficient investments. This paper shows that a seller invests efficiently when each seller offers latent contracts designed to exclude any other seller from trade (i. e. most intense competition). Because competition among sellers allows the buyer to appropriate part of the gains from his investment, the hold-up problem vanishes for most of the buyer's investment costs. However, the seller appropriates more than his marginal contribution to the gains from trade, and over-invests, when a group of sellers does not offer latent contracts (under less intense competition). Therefore, efficient investments can only be implemented when competition is at its most intense. © 2020 Walter de Gruyter GmbH, Berlin/Boston 2020.